Investigating Modern Islamic Boarding School Teachers’ Attitudes and Perceptions of World Englishes in an Indonesian Context - Hanif,; Kurniawati,; Maulizan ZA,; Rizki, Dini; Sitomorang, Nurjanius (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to investigate the perceptions and instructional practices of Modern Islamic Boarding school English teachers in North Aceh and Lhokseumawe, Indonesia, concerning the concept of World Englishes (WE). Employing a qualitative research design, data were gathered through semi-structured interviews and document analysis. The participants consisted of twelve English teachers representing different Modern Islamic boarding schools in North Aceh and Lhokseumawe. The collected data were analyzed using qualitative procedures.The findings reveal that while teachers acknowledge the presence of diverse English varieties, their understanding of the theoretical foundations and pedagogical implications of World Englishes remains limited. The majority of teachers continue to prioritize inner-circle varieties, particularly American and British English, as the primary instructional models. This preference is influenced by factors such as curriculum constraints, limited exposure to global English varieties, and students’ relatively low levels of English proficiency. As a result, the integration of World Englishes into classroom practice is still minimal.The study recommends the implementation of focused professional development initiatives to enhance teachers’ sociolinguistic awareness and pedagogical competence in addressing English variation. The gradual inclusion of non-native English varieties in teaching materials may contribute to more inclusive, authentic, and globally responsive English language instruction in Indonesia.